The Effect of Using Colored Sand on Children’s Cognitive Development - Nur Aiman; Humaedi; Amrullah; Besse Nirmala (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2026)
This study aims to enhance children’s cognitive development in color recognition, specifically their ability to name, point to, and group various colors, which has not yet developed as expected. The research method used is quantitative research of the experimental type. The research subjects consisted of all 15 children in Group B of Al-Khairaat Rarampadende Kindergarten. Data collection was conducted through observation of the children’s cognitive abilities before and after the intervention, which involved playing with colored sand. The data were analyzed by comparing the children’s cognitive development results before and after the intervention. The results of the study showed that before the intervention, no children (0%) were in the Very Well Developed (BSB) category; 11% of the children were in the Developing as Expected (BSH) category; 75.6% were in the Beginning to Develop (MB) category; and 13.3% were in the Not Yet Developed (BB) category ).After receiving treatment using colored sand, the children’s cognitive development improved, with 40% of children in the BSB category, 51% in the BSH category, 9% in the MB category, and none (0%) in the BB category. Based on these research results, the statistical test revealed a calculated t-value of 12.961 with a significance level of 0.001 (< 0.05), thus accepting the alternative hypothesis (H1) and rejecting the null hypothesis (H0). These findings indicate that play-based learning media using concrete objects can help children become more active, understand color concepts more easily, and increase their engagement in the learning process. It can be concluded that the use of colored sand influences the cognitive development of children in Group B. Colored sand media can help children recognize colors more easily, increase their interest in learning, and create an active and enjoyable learning atmosphere.